The Impact of Food Insecurity on Domestic Child Violence - Dwi Hadya Jayani; Dwini Handayani (Journal of Indonesian Applied Economics, 2024)
Purpose This research aims to examine the impact of food insecurity on the probability of child violence within households. Design/methodology/approach The study uses logistic regression analysis to establish the association between the dependent variable (child violence) and the independent variable (food insecurity) while controlling for several variables. The variables related to food insecurity are found in the National Socioeconomic Survey (Susenas) KOR 2020, while the variables associated with child violence are present in the Social Resilience Module of the September 2020 Susenas. The unit of analysis in this research is children aged 0-17 years, with the scope of the study focusing on households included in both Susenas KOR 2020 and the Social Assistance Module 2020 conducted by the Central Statistics Agency (Badan Pusat Statistik). After data merging, the sample used in this analysis comprises 40,231 households considered representative.   Findings Descriptive analysis indicates that food insecurity still frequently occurs in households with the highest expenditures, although the percentage is not as high as in the lowest quintile group (the poor). Based on logistic regression analysis, there is a significant association between food insecurity and child violence within households. However, there is a different pattern in the "Severe" food insecurity level, where the probability of child violence is lower compared to other levels of food insecurity.   Research limitations/implications Child violence in this study is based on the admission of adult household members (aged 17 and above) who perpetrate violence against children (aged under 17) and does not specify the type of violence that occurs.   Originality/value The research gap in this study is the occurrence of child violence based on expenditure groups and food insecurity. Additionally, the unit of analysis in this study is children aged 0-17 years within the scope of household research included in the 2020 National Socio-Economic Survey (Susenas KOR) and the 2020 Social Assistance Module (Modul Hansos) conducted by the Central Statistics Agency (Badan Pusat Statistik).